Experience with Eucaltptus grandis in Kerala State - Chandrasekharan, C. (Indian Forester, 1968)
Ecualyptus grandis was introduced in Kerala, primarily for afforesting the grasslands of the High Ranges. This species can grow in a wide range of climatic and soil conditions, so long as the land in which it grows is well drained. Therefore, Eucalyptus grandis has now emerged, as the most important species for industrial plantations in Kerala. Large areas are now being planted with the species, after clear-felling the natural forests. Up to 1968, the Kerala Forest Department has planted a total area of about 14,500 hectares with Eucalyptus grandis. Techniques and economics of raising Eucalyptus grandis plantations have been discussed in this paper. Its merits as a good "pay-master" has been indicated. For a country where the proper and suitable raw material for pulp and paper industry is scarce, Eucalyptus grandis has brought new hopes. It has been found to be a suitable raw material for pulp, paper and newsprint industries. The very fast growing nature of the species has added to its merits.